2009
DOI: 10.4156/jdcta.vol3.issue3.17
|View full text |Cite
|
Sign up to set email alerts
|

Content Transfer and Supporting Technologies in a Home Environment over Next Generation Convergence Home Network - From Vital Information Transfer to Broadband Content Transfer

Abstract: The world is facing the problem of rapid aging which is raising the concerns of individuals and governments as to how people, especially the elderly, can have comfortable, healthy, safe, and convenient lives. Information and Communication Technology (ICT) will play an important role in realizing the environment needed. This paper overviews, for the home environment, content transfer ranging from vital information transfer to broadband content transfer; we focus mainly on the viewpoint of network/transmission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Compared with other wireless network techniques, the only weakness of ZigBee is the low transmission rate. However, the low speed applications are easier to control than the rapid ones [6][7][8]. Smart home network is characterized by relatively few communication nodes within a 60 to 500 m 2 area, in which each node only communicates every 5 to 15 minutes.…”
Section: Wireless Technologiesmentioning
confidence: 99%
“…Compared with other wireless network techniques, the only weakness of ZigBee is the low transmission rate. However, the low speed applications are easier to control than the rapid ones [6][7][8]. Smart home network is characterized by relatively few communication nodes within a 60 to 500 m 2 area, in which each node only communicates every 5 to 15 minutes.…”
Section: Wireless Technologiesmentioning
confidence: 99%
“…Our laboratory has been researching several CPS related systems and applications that mainly focus on the vital human information captured by wearable sensor(s) [1,2] and environmental information capture [3,4]. In our research on environmental information capture, we found that human presence recognition is one of the key pieces of information needed in managing the environment, and ensuring security.…”
Section: Introductionmentioning
confidence: 96%